EVALUASI SIMPANG BERSINYAL PADA JALAN PUPUK RAYA – JALAN CIPTO MANGUNKUSUMO – JALAN SLAMET RIYADI – JALAN ARIEF RAHMAN HAKIM DI KOTA BONTANG MENGGUNAKAN SOFTWARE KAJI - IQBAL JANUAR, ENTJE (KURVA S JURNAL MAHASISWA, 2014)
Based on the conclusions of the suggestions in the study of this intersection is ;1. Condition of the junction of Jalan Cipto Mangunkusumo - Fertilizer Jalan Raya - Jalan Slamet Riyadi - Jalan Arief Rahman Hakim in Bontang evaluated peak hours resulted in improvements to the performance of the traffic delay . Improvements made to the phase and cycle time APILL , because the phase and cycle time APILL differ between the hours of peak and average hours then APILL must be modified in order to change automatically at peak hours to avoid long delays which were in- vehicle platoon .2. Conditions crossing on average hours crossroads where traffic volume is expected to be in stable condition, the driver must remain vigilant and follow the rules APILL phase and cycle time .3. The existence of a phase and cycle time improvements to APILL the relevant parties in this case the Department of Transportation Bontang should always evaluate the APILL .